The new Westminster dictionary of church history - Benedetto, Robert, 1950-; Duke, James O. (Louisville, Ky. : Westminster John Knox Press, 2008)
Jerald Bauer's Westminster Dictionary of Church History was originally published in 1969 and has ably served an entire generation of pastors, students, and scholars over the last decades of the twentieth century. In recognition of both the dictionary's age and the latest developments in patristics and other fields of study, Westminster John Knox Press commissioned this volume to continue in the previous work's tradition by providing up-to-date and immediate, authoritative, and introductory definitions and explanations of the major personalities, events, facts, and movements in the history of Christianity. Volume One covers the early, medieval, and Reformation periods and contains nearly fourteen hundred articles written by more than two hundred contributors. Volume Two will cover the modern period, from 1700 on. - Publisher.
v. 1. The early, medieval, and Reformation eras.
Rev. ed. of: The Westminster dictionary of church history. 1971.
Includes bibliographical references.
Keywords: Church history -- Dictionaries; Church history; Dictionaries